2015
DOI: 10.1155/2015/528753
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Drug-Eluting Stents in Patients Presenting with Acute ST-Segment Elevation Myocardial Infarction

Abstract: Background. Drug-eluting stents (DES) have proven clinical superiority to bare-metal stents (BMS) for the treatment of patients with ST-segment elevation myocardial infarction (STEMI). Decision to implant BMS or DES is dependent on the patient's ability to take dual antiplatelet therapy. This study investigated factors associated with DES placement in STEMI patients. Methods. Retrospective analysis was performed on 193 patients who presented with STEMI and were treated with percutaneous coronary intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our study, we also observed low rates of drug‐eluting stents among groups with cannabis use. There is evidence that bare‐metal stent use was more prevalent among patients with illicit drug use, and we speculate that this may be related to concerns about adherence to dual antiplatelet therapy postprocedure as failure to take dual antiplatelet therapy may result in stent thrombosis. While there is growing legalisation of marijuana in America, it has been at one point described a gateway to more dangerous illicit drug use .…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we also observed low rates of drug‐eluting stents among groups with cannabis use. There is evidence that bare‐metal stent use was more prevalent among patients with illicit drug use, and we speculate that this may be related to concerns about adherence to dual antiplatelet therapy postprocedure as failure to take dual antiplatelet therapy may result in stent thrombosis. While there is growing legalisation of marijuana in America, it has been at one point described a gateway to more dangerous illicit drug use .…”
Section: Discussionmentioning
confidence: 93%
“…The findings from these articles collectively demonstrate the existence of racial disparities in access to PCI, door-to-balloon time, procedure utilization, and clinical outcomes among elderly patients in America [ 14 ]. African American and Hispanic patients were consistently found to experience delays in accessing PCI, longer door-to-balloon times, and lower rates of procedure utilization compared to their White counterparts [ 15 ]. Moreover, racial and ethnic minorities had worse clinical outcomes, including higher mortality rates and an increased risk of major adverse cardiovascular events [ 1 - 4 , 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…Olafiranye et al (2015) observed that African American and Hispanic patients experienced worse outcomes compared to Caucasian patients [1]. These findings suggest that race may play a significant role in influencing long-term safety and efficacy outcomes following PCI, potentially leading to disparities in cardiovascular health among older patients [1,13,[15][16][17][18][19][20][21].…”
Section: Racial Disparities In Long-term Outcomesmentioning
confidence: 99%